2018
DOI: 10.1016/j.compscitech.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale approach for identification of transverse isotropic carbon fibre properties and prediction of woven elastic properties using ultrasonic identification

Abstract: In this work the possibility to reverse engineer the transverse isotropic carbon fibre properties from the 3D homogenized elastic tensor of the UD ply for the prediction of woven ply properties is explored. Ultrasonic insonification is used to measure the propagation velocity of both the longitudinally and transversally polarized bulk waves at various symmetry planes of a unidirectional (UD) Carbon/Epoxy laminate. These velocities and the samples' dimensions and density are combined to obtain the full 3D ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The results following the second stage of the inversion are summarized in the fourth column of Table 3 and the match between the experimental polar plot and prediction based on the inversion parameters is visualized by a difference amplitude polar plot in Figure 12b. A comparison of the associated elastic engineering constants (in the notation E ii , ν ij and G ij ) with values obtained and estimated from literature [24][25][26] (last three columns of Table 3) reveals that the inverted elasticity constants are within the expected range for a unidirectional carbon-epoxy material. In the study of Degrieck [24], these engineering constants are obtained through tensile tests of a UD C/E plate with a similar fiber volume fraction V f of approximately 55% as used here.…”
Section: Stage Ii: Viscoelastic Characterizationmentioning
confidence: 67%
See 1 more Smart Citation
“…The results following the second stage of the inversion are summarized in the fourth column of Table 3 and the match between the experimental polar plot and prediction based on the inversion parameters is visualized by a difference amplitude polar plot in Figure 12b. A comparison of the associated elastic engineering constants (in the notation E ii , ν ij and G ij ) with values obtained and estimated from literature [24][25][26] (last three columns of Table 3) reveals that the inverted elasticity constants are within the expected range for a unidirectional carbon-epoxy material. In the study of Degrieck [24], these engineering constants are obtained through tensile tests of a UD C/E plate with a similar fiber volume fraction V f of approximately 55% as used here.…”
Section: Stage Ii: Viscoelastic Characterizationmentioning
confidence: 67%
“…A comparison of the associated elastic engineering constants (in the notation E ii , ν ij and G ij ) with values obtained and estimated from literature [24][25][26] (last three columns of Table 3) reveals that the inverted elasticity constants are within the expected range for a unidirectional carbon-epoxy material. In the study of Degrieck [24], these engineering constants are obtained through tensile tests of a UD C/E plate with a similar fiber volume fraction V f of approximately 55% as used here. Italic values represent estimations of parameters which cannot be determined by the experimental technique.…”
Section: Stage Ii: Viscoelastic Characterizationmentioning
confidence: 67%
“…This MNA effect plays an important role during the shape programming process where large deformation occurs under a temperature of 70 °C. For this reason, the axial direction elastic modulus was measured from the tensile test at the elevated temperature of 70 °C, and the other material properties of SMPC were referred and estimated by previous studies as shown in Table S2. The boundary condition of the bending test is shown in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…When defining the effective mass density of the ply, the rule of mixture is applied, assuming a density of the carbon fibers of 1800 ∕ 3 . The stiffness matrix for each ply is calculated by the Chamis model [57] from the properties of carbon fiber [58] and epoxy matrix. The longitudinal wave velocity propagating in the thickness direction is then calculated from the stiffness matrix.…”
Section: Simulation Parametersmentioning
confidence: 99%